2021
DOI: 10.34172/ijhpm.2021.25
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Markets and Policy Responses in Southeast Asia: A Scoping Review

Abstract: Background: The global e-cigarette market has proliferated and is increasingly dominated by transnational tobacco companies. While Southeast Asian countries have received relatively little attention in e-cigarette research, the region represents an area of potentially untapped growth for the industry. We review the e-cigarette situation in Southeast Asia in terms of the e-cigarette markets, advertising and promotion of e-cigarettes, reported health impacts of e-cigarette use, and policy responses in the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 76 publications
0
32
0
3
Order By: Relevance
“…This is of particular concern because of the large youth populations in countries that have been the target of e-cigarette industry ambitions ( 23 ). Emerging evidence suggests the prevalence of online e-cigarette marketing: A recent report on Indonesia, which has a nascent, fast-growing e-cigarette market ( 24 ) and a large population of youth active online ( 25 ), found that e-cigarette marketing was prevalent on social media platforms and used a range of youth-oriented tactics to promote the use of e-cigarettes and their components ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular concern because of the large youth populations in countries that have been the target of e-cigarette industry ambitions ( 23 ). Emerging evidence suggests the prevalence of online e-cigarette marketing: A recent report on Indonesia, which has a nascent, fast-growing e-cigarette market ( 24 ) and a large population of youth active online ( 25 ), found that e-cigarette marketing was prevalent on social media platforms and used a range of youth-oriented tactics to promote the use of e-cigarettes and their components ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the tobacco and nicotine business has changed significantly, especially with the emergence of new tobacco products. Although debates about the long-term health effects of new tobacco products and their effectiveness as a smoking cessation aid are ongoing [1], it has been concluded that all new tobacco products are in fact highly addictive and pose health risks; Bigwanto et al Substance Abuse Treatment, Prevention, and Policy (2022) 17:78 therefore, these products should not be accessed and used by youth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are differences in how countries regulate e-cigarettes. A scoping review study of ecigarette policy responses in Southeast Asia reported that 10 out of 12 countries regulate products, with ve countries totally banning the products and only two countries reporting no speci c regulation, except for scal policy, one of which is Indonesia [14] The Indonesian government currently has no speci c regulation for the products, the only regulation that existed is an excise tax imposed on the products [15], which makes the control of the products in the country very weak, including the promotion in the media.…”
Section: Introductionmentioning
confidence: 99%